Relationships between Extension Competencies, Organisational Commitment and Job Satisfaction with Performance of Agricultural Extension Workers in Yemen - Khalil, Ali Hassan Obaid (2008)
This study aimed to determine the relationships between selected variables, namely extension competencies including human development competencies, leadership development, extension communication methods, programme development, programme implementation and programme evaluation; organisational commitment as well as job satisfaction and job performance of agriculture extension workers. The study also sought to identify the best predictors of job performance of the extension workers. The total population of the extension workers was 1364. The sample size of this study was 300 which were determined by using Cochran's formula (1977). The study used stratified random sampling technique in which 300 respondents from the agriculture extension services organisations in Yemen were chosen. A complete list of agriculture extension workers across the three agriculture regions, namely, coastal, highlands and desert regions was obtained. The research design of this study was a descriptive correlational study. Self-administered questionnaire was used as the research instrument to collect data from the respondents of this study. The quantitative data were analysed by using descriptive statistics such as mean and standards deviations. The parametric statistics such as Pearson correlation, multiple regression analyses, t-test and ANOVA also were used. From the descriptive analysis, the result show that the overall extension workers performance illustrated with mean score (M = 2.88) and standard deviation (SD = 0.69), that more than a half (60.7 %) of the respondents experienced a moderate level of job performance, while 23.8 % of them indicated a low level of performance and 15.5% considered a high level of performance. Furthermore, the findings from parametric analysis indicated that there were significant relationships between the independent variables and job performance of extension workers. The independent variables are as follows: extension programme implementation competencies, extension programme planning competencies, extension programme evaluation competencies, organisational commitment, and job satisfaction. Multiple regression analysis was used to identify the best predictors of extension workers’ performance. The variables according to descending order are job satisfaction (Beta = 0.431), extension programme planning competencies (Beta = 0.239), extension programme implementation competencies (Beta = 0.147), extension programme evaluation competencies (Beta = 0.145), and organisational commitment (Beta = 0.102). The predictors explained 60.6 % variance (F = 54.008, p = 0.0001) of job performance. The study is important as it would become a platform for future research to consider aspect of performance and its variants. The implementation of human resource development initiatives is very important to consider by the relevant agencies in order to improve extension workers’ competencies and performance. This study also signals the importance of ensuring good and motivated work environment for extension workers for achieving a high performance. Extension services should also realise the various contributors of job performance, some of them are based on the individual factors as found in this study. By knowing these factors, they would be used as inputs in the recruitment, selection and succession planning processes in order to get the right extension workers. This will make extension workers know clearly their duties, tasks, and how to act in rural community. To support the findings of this study in the country, it is recommended that future studies are conducted across employees from other rural development organisations including agricultural and community development organisations by taking into considerations other work behaviour and social factors that might help more to understand the individual performance phenomenon.